(untitled) (Journal of Enam Medical College, 2018)
Background: Atorvastatin and rosuvastatin are two widely used HMG-CoA reductase inhibitors (statins). These are used as lipid-lowering drugs to reduce atherosclerosis-induced cardiovascular events. The beneficial effects of statins also involve some lipid-independent mechanisms which include modification of thrombus formation and degradation, alteration in inflammatory response, plaque stabilization and improvement of endothelial function. Objective: To compare antithrombogenic effect of atorvastatin and rosuvastatin in patients with hyperlipidemia. Materials and Methods: A prospective, open-labeled, interventional, randomized and single-center study was carried out in Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March, 2016 to August, 2017 on 52 hyperlipidemic patients. After randomization patients were assigned to atorvastatin 10 mg or rosuvastatin 5 mg daily for 8 weeks. Blood was collected at baseline and after intervention to measure platelet count, prothrombin time (PT) and serum lipid profile. Results: The baseline characteristics of patients treated with atorvastatin and rosuvastatin were almost identical. The platelet count in atorvastatin group was reduced after intervention (2.30%, p=0.463) which was not significant but in rosuvastatin group platelet count reduced significantly (12.33%, p=0.021) after intervention. There was no statistically significant difference (p=0.187) between the two statin treated groups. PT was increased significantly after intervention in both atorvastatin group (31.44%, p<0.001) and in rosuvastatin group (31.93%, p=0.003), which was statistically significant. No significant difference was observed between the two groups (p=0.573). Both atorvastatin and rosuvastatin significantly improved serum lipid profile. Conclusion: The present study reveals that rosuvastatin reduced thrombogenesis more effectively than atorvastatin in hyperlipidemic patients. J Enam Med Col 2018; 8(3): 153-158